2014
DOI: 10.1111/1750-3841.12549
|View full text |Cite
|
Sign up to set email alerts
|

Flavor‐Enhancing Properties of Mushrooms in Meat‐Based Dishes in Which Sodium Has Been Reduced and Meat Has Been Partially Substituted with Mushrooms

Abstract: The effects of beef substitution with crimini or white mushrooms (Agaricus bisporus) on the flavor profiles of carne asada and beef taco blends were measured with a descriptive analysis panel. Sensory mitigation of sodium reduction through the incorporation of mushrooms was also investigated in the taco blends. The substitution of beef with mushrooms in the carne asada did not alter the overall flavor strength of the dish, but the incorporation of 50% or 80% ground mushroom in the beef taco blend did enhance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 20 publications
0
37
0
1
Order By: Relevance
“…For example, the concept could be tested in settings more realistic than the laboratory, such as a dining hall, café, or restaurant. In addition, it was shown that mushrooms could be used for their natural flavor‐enhancing properties to carry out the swap from high‐meat to high‐vegetable without adding extra seasoning (micro‐ingredients; Myrdal Miller and others ; Guinard and others ). This same concept could be applied to other recipes, utilizing the flavors and textures inherently present in vegetables other than mushrooms, meaning vegetables themselves could potentially be a successful sensory strategy for the Flexitarian Flip™.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the concept could be tested in settings more realistic than the laboratory, such as a dining hall, café, or restaurant. In addition, it was shown that mushrooms could be used for their natural flavor‐enhancing properties to carry out the swap from high‐meat to high‐vegetable without adding extra seasoning (micro‐ingredients; Myrdal Miller and others ; Guinard and others ). This same concept could be applied to other recipes, utilizing the flavors and textures inherently present in vegetables other than mushrooms, meaning vegetables themselves could potentially be a successful sensory strategy for the Flexitarian Flip™.…”
Section: Discussionmentioning
confidence: 99%
“…This research is part of the Healthy Flavors Research Initiative, a collaboration between the Culinary Institute of America (CIA) and UC Davis with the objective of exploring culinary and flavoring techniques to maintain the sensory appeal to consumers when ingredients considered less healthy are replaced with healthier, plant‐based ingredients. This concept was studied specifically with beef and mushrooms (Myrdal Miller and others ; Guinard and others ). The CIA and UC Davis found that substituting 50% or even 80% of the beef with ground white mushrooms could enhance the overall flavor of a beef taco blend and maintain consumer acceptance ratings (Myrdal Miller and others ; Guinard and others ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mushrooms are high in protein, carbohydrates, and dietary fiber but low in fat and energy (Guinard et al., ). Mushrooms can be used as healthy substitutes for sodium in meat‐based dishes, phosphates in emulsion‐type sausages, and the nitrite in emulsion‐type sausage (Choe et al., ; Ghobadi, Mohammadi, Chabavizade, & Sami, ; Myrdal Miller et al., ). Pleurotus eryngii (king oyster mushroom) is an edible and medicinal mushroom in the family Pleurotaceae and phylum Basidiomycota (Xu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A low proportion of I + G (0.9% to 1.3%) can make the chicken seasoning more umami when it is combined with MSG. [38,39] The I + G content in sample AL was slightly higher than in sample AB. Almost 50% of all the samples is chloride, which is one of the major taste components of chicken seasonings.…”
Section: Msg I + G and Chloridementioning
confidence: 88%